The Red Supergiant Progenitor Luminosity Problem - Emma R. Beasor; Nathan Smith; Jacob E. Jencson (The Astrophysical Journal)
Analysis of pre-explosion imaging has confirmed red supergiants (RSGs) as the progenitors to Type II-P supernovae (SNe). However, extracting an RSG's luminosity requires assumptions regarding the star’s temperature or spectral type and the corresponding bolometric correction, circumstellar extinction, and possible variability. The robustness of these assumptions is difficult to test since we cannot go back in time and obtain additional pre-explosion imaging. Here, we perform a simple test using the RSGs in M31, which have been well observed from optical to mid-IR. We ask the following: By treating each star as if we only had single-band photometry and making assumptions typically used in SN progenitor studies, what bolometric luminosity would we infer for each star? How close is this to the bolometric luminosity for that same star inferred from the full optical-to-IR spectral energy distribution (SED)? We find common assumptions adopted in progenitor studies systematically underestimate the bolometric luminosity by a factor of 2, typically leading to inferred progenitor masses that are systematically too low. Additionally, we find a much larger spread in luminosity derived from single-filter photometry compared to SED-derived luminosities, indicating uncertainties in progenitor luminosities are also underestimated. When these corrections and larger uncertainties are included in the analysis, even the most luminous known RSGs are not ruled out at the 3 σ level, indicating there is currently no statistically significant evidence that the most luminous RSGs are missing from the observed sample of II-P progenitors. The proposed correction also alleviates the problem of having progenitors with masses below the expected lower-mass bound for core collapse.